PENGARUH INSIDER OWNERSHIP, STRUKTUR MODAL, KEBIJAKAN HUTANG DAN DEVIDEN TERHADAP NILAI PERUSAHAAN - Dodik Setiawan, 0525030070; Kartika, Andi (Students Journal of Accounting and Banking, 2013)
This study aims to identify and examine the effect of insider ownership, capital structure, debt and dividend policy on firm value. The population in thes study are all listed manufacturing campanies listed on the Indonesia Stock Exchane companies manufacturing research. The type of data used are secondary data from any manufacturing companies listed on the Indonesia Stock Exchane for the part 4 Yerad. Data were analyzed by Multiple Linear Regression.Â The results showed than insider ownership and capital structure negatively affect the value of the firm, while the debt policy has positive effect on firm value. DividendÂ Payout Ratio(DPR) has no effect on firm value.Keywords: insiderÂ ownership, capital structure, debt policy, dividend and corporate value